Use of Copy Number Deletion Polymorphisms to Assess DNA Chimerism. (1st August 2014) - Bruno, Damien L; Ganesamoorthy, Devika; Thorne, Natalie P; Ling, Ling; Bahlo, Melanie; Forrest, Sue; Veenendaal, Marieke; Katerelos, Marina; Skene, Alison; Ierino, Frank L; Power, David A; Slater, Howard R
Abstract: BACKGROUND: We describe a novel approach that harnesses the ubiquity of copy number deletion polymorphisms in human genomes to definitively detect and quantify chimeric DNA in clinical samples. Unlike other molecular approaches to chimerism analysis, the copy number deletion (CND) method targets genomic loci (>50 base pairs in length) that are wholly absent from wild-type (i.e., self) background DNA sequences in a sex-independent manner. METHODS: Bespoke quantitative PCR (qPCR) CND assays were developed and validated using a series of DNA standards and chimeric plasma DNA samples collected from 2 allogeneic kidney transplant recipients and 12 pregnant women. Assay performance and informativeness were assessed using appropriate statistical methods. RESULTS: The CND qPCR assays showed high sensitivity, precision, and reliability for linear quantification of DNA chimerism down to 16 genomic equivalents (i.e., 106 pg). Fetal fraction (%) in 12 singleton male pregnancies was calculated using the CND qPCR approach, which showed closer agreement with single-nucleotide polymorphism–based massively parallel sequencing than the SRY (sex determining region Y) (Y chromosome) qPCR assay. The latter consistently underestimated the fetal fraction relative to the other methods. We also were able to measure biological changes in plasma nonself DNA concentrations in 2 renal transplant recipients. CONCLUSIONS: The CND qPCR technique is suitable for measurement of chimerism for monitoring of rejection in allogeneic organ transplantation and quantification of the cell-free fetal DNA fraction in maternal plasma samples used for noninvasive prenatal genetic testing.